Circadian period and the timing of melatonin onset in men and women: predictors of sleep during the weekend and in the laboratory. (6th December 2012) - Lazar, Alpar S.; Santhi, Nayantara; Hasan, Sibah; Lo, June C.‐Y.; Johnston, Jonathan D.; Von Schantz, Malcolm; Archer, Simon N.; Dijk, Derk‐Jan
Summary: Sleep complaints and irregular sleep patterns, such as curtailed sleep during workdays and longer and later sleep during weekends, are common. It is often implied that differences in circadian period and in entrained phase contribute to these patterns, but few data are available. We assessed parameters of the circadian rhythm of melatonin at baseline and in a forced desynchrony protocol in 35 participants (18 women) with no sleep disorders. Circadian period varied between 23 h 50 min and 24 h 31 min, and correlated positively ( n = 31, r s = 0.43, P = 0.017) with the timing of the melatonin rhythm relative to habitual bedtime. The phase of the melatonin rhythm correlated with the Insomnia Severity Index ( n = 35, r s = 0.47, P = 0.004). Self‐reported time in bed during free days also correlated with the timing of the melatonin rhythm ( n = 35, r s = 0.43, P = 0.01) as well as with the circadian period ( n = 31, r s = 0.47, P = 0.007), such that individuals with a more delayed melatonin rhythm or a longer circadian period reported longer sleep during the weekend. The increase in time in bed during the free days correlated positively with circadian period ( n = 31, r s = 0.54, P = 0.002). Polysomnographically assessed latency to persistent sleep ( n = 34, r s = 0.48, P = 0.004) correlated with the timing of the melatonin rhythm when participants were sleeping at their habitual bedtimes in the laboratory. This correlation was significantly stronger in women than in men ( Z = 2.38, P = 0.017). The findings show that individual differences in circadian period and phase of the melatonin rhythm associate with differences in sleep, and suggest that individuals with a long circadian period may be at risk of developing sleep problems.